Enumeration and functional investigation of endothelial progenitor cells in neovascularization of diabetic foot ulcer rats with a Chinese 2‐herb formula 中国一种包含两种草药的复方对大鼠糖尿病足溃疡新血管形成中内皮组细胞数量和功能影响的研究. (17th December 2014) - Tam, Jacqueline Chor Wing; Ko, Chun Hay; Lau, Kit Man; To, Ming Ho; Kwok, Hin Fai; Siu, Wing Sum; Lau, Ching Po; Chan, Wai Yee; Leung, Ping Chung; Fung, Kwok Pui; Lau, Clara Bik San
Abstract: Backbround: We investigated the effect of a Chinese 2‐herb formula (NF3) on the enumeration and angiogenic differentiation of endothelial progenitor cells (EPCs) in diabetic foot ulcer rats. Methods: EPCs and stromal cell‐derived factor‐1α (SDF‐1α) were quantified by flow cytometry and ELISA, respectively. In vitro angiogenesis assays included proliferation, adhesion, migration and tube formation. Results: Our result demonstrated that NF3 (0.98 g/kg) could significantly enhance the circulating CD34 + /VEGFR2 + /CD45 − EPCs levels in diabetic foot ulcer rats by 60% ( P < 0.05) through the partial elevation of SDF‐1α, restoring the mobilization ability of EPCs for wound neovascularization. We successfully isolated the BM‐derived EPCs to study their angiogenic potential after NF3 treatment. BM‐derived EPCs significantly expressed cell surface markers of CD34, CD146 and VEGFR2 ( P < 0.05 − 0.01). NF3 could significantly stimulate the proliferation and attachment ability of EPCs dose‐dependently ( P < 0.01–0.001). Besides, NF3 could significantly augment EPCs migration ( P < 0.001) and tube formation ( P < 0.01–0.001). Conclusions: NF3 modulated diabetic wound healing through regulation of systemic EPCs level and increase in local vascular formation.